Development and Effects of a Chatbot to Support Health Assessment Practicum - Soo Jung Choi; Geunhee Lee; Yun Hee Shin (Journal of Fundamental Nursing Science, 2026)
Purpose: This study aimed to develop a question-and-answer chatbot that enables nursing students to obtain immediate information during self-directed practice and to evaluate its effects. Methods: The chatbot was developed through analysis, design, implementation, and evaluation. Its effects were evaluated using a nonequivalent control group post-test design. Fifty-five students were assigned to the experimental group, and 56 students were assigned to the control group. The experimental group used the developed chatbot to obtain answers to questions during self-directed practice, whereas the control group used the conventional question-and-answer method. Results: The chatbot was built using a question-and-answer database that categorized responses according to user intent, and the "Health Assessment Skills Up" chatbot channel was created and operated. Expert evaluation found no major usability problems, although modifications were made to reflect expert feedback. The control group scored significantly higher than the experimental group on musculoskeletal examination skills. No significant betweengroup differences were found for other variables. However, qualitative feedback from the experimental group indicated that the chatbot was perceived as a useful auxiliary tool for self-directed learning because it provided accessible support regardless of time and place. Conclusion: Although statistically significant between-group differences were not found for most outcomes, students evaluated the chatbot positively as an accessible learning support tool. These findings suggest that the chatbot may be useful in nursing practice education by providing immediate information during self-directed practice.